THE EFFECT OF RETURN ON ASSETS (ROA), NET PROFIT MARGIN (NPM), TOTAL ASSET TURNOVER (TATO), AND STOCK PRICE ON DIVIDEND POLICY IN MANUFACTURING COMPANIES LISTED ON IDX 2016-2020 - Batubara, Maisara; Mery Susanty; Elisha Anggreani; Felani Valentine (SEAN Institute, 2022)
The purpose of this study is to see the effect of Return On Assets (ROA), Net Profit Margin (NPM), Total Asset Turnover (TATO) and Stock Price on Dividend Policy in Manufacturing Companies Listed on the IDX 2016-2020. both partially and simultaneously. Dividend policy is a decision whether the profit earned by the company will be distributed to shareholders as dividends or will be retained in the form of retained earnings for future investment financing. Each company will announce its dividend policy to the public and the dividend announcement is one of the information that the market will respond to, because dividends are considered an indicator of the company's prospects so that they affect the value of the company. An increase in dividend payments shows a good signal and the market will certainly respond positively. Conversely, company policy in reducing dividend payments will give a bad signal and as a result the market will react negatively. The population in the study has all manufacturing companies listed on the IDX for the 2016-2020 period, namely 177 companies and samples with a total of 150 units of analysis. The research method applies multiple linear regression analysis techniques. The results of the study are Return On Assets (ROA), Net Profit Margin (NPM), Total Asset Turnover (TATO) and Stock Price partially and jointly affect the Dividend Policy in Manufacturing Companies Listed on the IDX 2016-2020.